1994
DOI: 10.1016/0266-7681(94)90238-0
|View full text |Cite
|
Sign up to set email alerts
|

Double and Multiple Looped Suture Tendon Repair

Abstract: We report our experience of using double or multiple looped sutures for primary tenorrhaphy combined with early active mobilization. In 46 patients involving 51 fingers with flexor tendon lacerations, double threads of the looped nylon suture were placed to repair injured FDP or FDS tendons, or three threads of looped nylon suture were made to repair the FDP tendons. Using White's (1956) criteria, the results were good or excellent in 76.5% of fingers. The double and multiple looped sutures are of sufficient s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
99
0
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(102 citation statements)
references
References 12 publications
0
99
0
3
Order By: Relevance
“…2D, g) (23,38), and Tsuge ( Fig. 3A, B) (39,40) repairs have demonstrated improved gap and ultimate forces compared to the respective 2-strand techniques (Table 1). Increasing the number of strands also improved the yield force and stiffness in the Pennington modified Kessler and Savage repairs (23, 41) (Table 1).…”
Section: Core Sutures Number Of Strandsmentioning
confidence: 94%
“…2D, g) (23,38), and Tsuge ( Fig. 3A, B) (39,40) repairs have demonstrated improved gap and ultimate forces compared to the respective 2-strand techniques (Table 1). Increasing the number of strands also improved the yield force and stiffness in the Pennington modified Kessler and Savage repairs (23, 41) (Table 1).…”
Section: Core Sutures Number Of Strandsmentioning
confidence: 94%
“…Emphasis on the needs and application of fouror six-strand core repairs in clinical tendon repairs appeared first in Savage and Risitano's report [11] in the late 1980s, followed by the report of Tang et al [20] in 1994, and then a series of reports in Atlas of Hand Clinics by Taras [21], Sandow and McMahon [22], and Lim and Tsai [23] in 1996. Tang et al [20] reported using double-or multiplelooped sutures for primary tendon repairs with combined early active and passive mobilization for 3 weeks.…”
mentioning
confidence: 99%
“…Wang és mtsai [7] módosították az eredeti, 6 öltéses Tang-módszert [8], a varrathoz egy harántöl-tést hozzáadva, így egy "M" konfigurációt formálva az öltéssel, amely kevesebb öltést és csomót jelentett az ín felszínén (1. ábra). Kutatók másik csoportja ugyanakkor újabb varratformákat fejlesztett ki annak érdekében, hogy csökkentsék az ínvégek között, a mozgatás hatására kialakult résképződést.…”
Section: íNvarrattípusokunclassified